2019
DOI: 10.1042/bsr20190045
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of IGFBP2 mRNA predicts poor survival in patients with glioblastoma

Abstract: The prognosis of patients with glioblastoma (GBM) is dismal. It has been reported that Insulin-like growth factor (IGF) binding protein 2 (IGFBP2) is associated with the mobility and invasion of tumor cells. We investigated the expression of IGFBP2 mRNA in GBMs and its clinical relevance, using tissue microarrays and RNAscope in situ hybridization in 180 GBMs and 13 normal or edematous tissues. The correlations between the expression and clinical pathological parameters as well as some other biomarkers were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 24 publications
6
25
0
Order By: Relevance
“…VM has been considered as one of the reasons that GBM becomes resistant to anti-VEGF therapy [ 30 ]. Our study confirmed significant up-regulation of IGFBP2 and predicted a poor outcome for patients as shown in previous studies [ 17 , 31 33 ], thus providing more evidence for further research into its functional roles during GBM progression. PTPRN is also located on the human chromosome 2 (2q35) but is interestingly down-regulated in GBM tissue and was associated with poor prognosis as the expression increased.…”
Section: Discussionsupporting
confidence: 90%
“…VM has been considered as one of the reasons that GBM becomes resistant to anti-VEGF therapy [ 30 ]. Our study confirmed significant up-regulation of IGFBP2 and predicted a poor outcome for patients as shown in previous studies [ 17 , 31 33 ], thus providing more evidence for further research into its functional roles during GBM progression. PTPRN is also located on the human chromosome 2 (2q35) but is interestingly down-regulated in GBM tissue and was associated with poor prognosis as the expression increased.…”
Section: Discussionsupporting
confidence: 90%
“…Innovative technologies could present more robust and reliable data leading to, for example revival and repurposing of ‘forgotten’ biomarkers. In the present study, RNAscope probe was used to detect the expression of IGFBP2 mRNA in 180 glioblastomas [11]. The analysis revealed 16.9 months median overall survival for the patients with low IGFBP2 mRNA levels, but only 11.6 months for patients with high IGFBP2 , which is a striking difference.…”
mentioning
confidence: 89%
“…Following a previous comparison of gene expression profiles between gliomas with different grades that revealed frequent overexpression of insulin-like growth factor binding protein 2 ( IGFBP2 ) in glioblastomas [12], Yuan et al [11] set out to investigate IGFPB2 mRNA levels in a larger cohort of glioblastomas. What is known about IGFBP2 in brain tumors?…”
mentioning
confidence: 99%
See 2 more Smart Citations